Genome‐wide analysis of carbohydrate‐active enzymes in Pyramimonas parkeae (Prasinophyceae). Issue 5 (21st August 2017) - Satjarak, Anchittha; Graham, Linda E.
Abstract : The wall‐less green flagellate Pyramimonas parkeae is classified in clade I of the prasinophytes, a paraphyletic assemblage representing the last common ancestor of Viridiplantae, a monophyletic group composed of the green algae and land plants. Consequently, P. parkeae and other prasinophytes illuminate early‐evolved Viridiplantae traits likely fundamental in the systems biology of green algae and land plants. Cellular structure and organellar genomes of P. parkeae are now well understood, and transcriptomic sequence data are also publically available for one strain of this species, but corresponding nuclear genomic sequence data are lacking. For this reason, we obtained shotgun genomic sequence and assembled a draft nuclear genome for P. parkeae NIES254 to use along with existing transcriptomic sequence to focus on carbohydrate‐active enzymes. We found that the P. parkeae nuclear genome encodes carbohydrate‐active protein families similar to those previously observed for other prasinophytes, green algae, and early‐diverging embryophytes for which full nuclear genomic sequence is publically available. Sequences homologous to genes related to biosynthesis of starch and cell wall carbohydrates were identified in the P. parkeae genome, indicating molecular traits common to Viridiplantae. For example, the P. parkeae genome includes sequences clustering with bacterial genes that encode cellulose synthases (Bcs), including regions coding for domains common to bacterial and plant cellulose synthases; these new sequences were incorporated into phylogenies aimed at illuminating the evolutionary history of cellulose production by Viridiplantae. Genomic sequences related to biosynthesis of xyloglucans, pectin, and starch likewise shed light on the origin of key Viridiplantae traits.